Observations and Fokker‐Planck Simulations of the L‐Shell, Energy, and Pitch Angle Structure of Earth's Electron Radiation Belts During Quiet Times. Issue 2 (18th February 2019) - Ripoll, J.‐F.; Loridan, V.; Denton, M. H.; Cunningham, G.; Reeves, G.; Santolík, O.; Fennell, J.; Turner, D. L.; Drozdov, A. Y.; Cervantes Villa, J. S.; Shprits, Y. Y.; Thaller, S. A.; et al.
Abstract: The evolution of the radiation belts in L ‐shell ( L ), energy ( E ), and equatorial pitch angle ( α 0 ) is analyzed during the calm 11‐day interval (4–15 March) following the 1 March 2013 storm. Magnetic Electron and Ion Spectrometer (MagEIS) observations from Van Allen Probes are interpreted alongside 1D and 3D Fokker‐Planck simulations combined with consistent event‐driven scattering modeling from whistler mode hiss waves. Three ( L, E, α 0 ) regions persist through 11 days of hiss wave scattering; the pitch angle‐dependent inner belt core ( L <2.2 and E < 700 keV), pitch angle homogeneous outer belt low‐energy core ( L > 5 and E < 100 keV), and a distinct pocket of electrons ( L [4.5, 5.5] and E [0.7, 2] MeV). The pitch angle homogeneous outer belt is explained by the diffusion coefficients that are roughly constant for α 0 <60°, E > 100 keV, 3.5 < L < L pp 6. Thus, observed unidirectional flux decays can be used to estimate local pitch angle diffusion rates in that region. Top‐hat distributions are computed and observed at L 3–3.5 and E = 100–300 keV. Plain Language Summary: We study the evolution of the radiation belts during quiet geomagnetic times from satellite observations and numerical codes. We reach a global understanding of the trapped electrons variation with time, space, energy, and pitch angle (the angle of the velocity vector with the magnetic field). We exhibit three stable regions, which are less sensitive to scattering from hiss waves, while, on the other hand, hiss causes flux decay over 12 days that forms the slot region between the inner and outer belt. The existing theory explains why the outer belt electron decay is independent of pitch angle but dependent upon energy. This implies that satellite observations can reveal local pitch angle diffusion rates, themselves intimately connected with the wave properties. Thus, a connection is made between observed wave properties and observed/computed scattered electron flux, consistent with theory. Regions where the flux is pitch angle dependent are isolated in the low‐energy slot region where we show that the real shape is a smoothed version of the ideal top‐hat distribution computed from theory. The impact of this work is improved understanding of the belt evolution for space weather prediction, with a proposed event‐driven method that accurately (within ×2) predicts the electron flux decay after storms. Key Points: Global computations of the ( L, E, α 0 ) structure of the evolving radiation belt during quiet times agree well with observations The inner belt decay is pitch angle dependent, while the outer belt is much more homogeneous with two distinct ( L, E ) regions The homogeneity of the pitch angle diffusion coefficient due to hiss waves explains the uniform outer belt decay and why 1D and 3D simulations agree